Fair, Rich, Happy, or Equal : What makes a society more stable? - Guzmán Illescas, David Arturo (2019)
In literature, there are four commonly used approaches trying to prove that through their application, they can achieve the goal of welfare maximization. These approaches are happiness, fairness, money possession, and equality. Unfortunately, so far, there is no indisputable answer as to which of them works the best. To help on this continues debate, the thesis is proposing a change of variable. Instead of measuring the level of welfare, the proposed variable called social stability, estimates the conformity of individuals with the circumstances they are living in. To enable its estimation a second proposition was the implementation of MIMIC models bases on the aforementioned approaches. With these two propositions, the thesis tries to answer which of the approaches has a greater impact on stability. Using the data from 109 countries in the year 2016, the obtained predictions of social stability show that, in this year, money possession had the most significant average effect on stability. And concerning the counties analyzed, the WEIRD countries were, on average, the more stable. However, the results cannot be considered reliable, as none of the models proved to be statistically significant. Nonetheless, some models did find significant relationships, which also were proved to be present in society, between social stability and other variables.